Patterns of activity evoked in cerebellar interpositus nuclear neurones by natural somatosensory stimuli in awake cats - Cody, Frederick W. J. (1981)
1. Stable extracellular unitary recordings were made from 138 cerebellar interpositus nuclear neurones (IPNs) in awake cats. Mean background discharge, in animals in a state of relaxed wakefulness and in the absence of overt movement, was 41·0±2·6 impulses/sec (mean±s.e.m). 2. Animals were trained to accept a variety of sensory testing procedures without producing detectable motor reactions. Mechanical taps (1 mm amplitude; 20 msec overall duration) applied to the main pads or dorsal surfaces of the forepaws and/or hind paws modified discharge in forty-eight of 110 IPNs tested. Response patterns to taps generally comprised one or more of three basic components, namely: short-latency excitation, e(1), at onset latencies of 13·0±0·9 msec (mean±s.e.m.) for ipsilateral forepaw (iF) and 17·0±0·7 msec for ipsilateral hind paw (iH); a period of reduced discharge, at latencies 25·6±2·6 msec for iF and 32·3±2·1 msec for iH; a delayed acceleration of discharge, e(2), at latencies 47·4±4·6 msec for iF and 46·4±4·1 msec for iH. The component e(1) was the most common (present in 80% of responses) and e(2) the least common (present in 18% of responses). 3. The majority (> 70%) of responses of IPNs to tap stimulation of the paws comprised net excitation. 4. Convergence of tap-evoked sensory input from iF and iH on to individual IPNs was evident in eight of the thirty-five units tested with stimulation of both afferent sites. 5. Approximately one third of IPNs so tested were sensitive to passive manipulation of limb joints in the quiet, awake cat. Sixteen of the forty-three IPNs so tested responded to displacement of the ipsilateral wrist and/or elbow joints and three of ten IPNs so tested responded to movement of contralateral forepaw joints. Corresponding proportions of IPNs responding to passive ankle and/or knee joint displacements were sixteen of thirty-six units tested and three of three units tested for ipsilateral and contralateral hind paws respectively. Convergence of input generated by manipulation of iF and iH joints on to individual IPNs was apparent in only three of twenty-four units tested at each site. 6. Tactile stimulation (brushing fur, gentle pressure on the skin) of iF influenced discharge in twelve of thirty-seven IPNs tested and comparable iH-related cutaneous sensory fields were found for fourteen of twenty-eight IPNs tested. 7. The modulations of discharge of IPNs associated with active movements of the stimulated limb were usually far more pronounced than those elicited by somatosensory stimulation in the quiet, relaxed animal. 8. Responses of IPNs to natural somatosensory stimulation in the awake cat are compared with those previously described for anaesthetized or decerebrate preparations and with those found for electrical stimulation of cutaneous nerves in awake cats. In general IPN response patterns to precisely timed tap stimulation of the paws in the awake animal closely resembled those that would have been predicted from the earlier studies, although the time course of responses differed in certain respects.